FRENECTOMY WITH Z PLASTY TECHNIQUE FOR HIGH ABERRANT FRENUM (FRENEKTOMI DENGAN TEKNIK Z-PLASTY PADA ABERANSIA FRENULUM YANG TINGGI - Andi Supriatna; Ira Komara (Journal of Health and Dental Sciences, 2022)
An aberrant frenum can cause gingival recession and plaque accumulation due to a muscle pull. It also presents an aesthetic problem and inhibits the orthodontic result in a case with midline diastema, thus causing a recurrence after the treatment. This case report describes how periodontal surgery can accomplish such an aberrant frenum like a frenectomy procedure. This case report shows the abnormal maxillary labial frenum removal in a 21-year-old through the Z-plasty technique. The Z Plasty was made with an angulation of about 60° on the left and right sides of the vertical incision to obtain a double rotational flap. The two flaps were then transposed to the opposite side of the apex of each flap for relief of soft tissue tension. This pattern has shown uneventful healing and minimized scar formation, which was favorable in aesthetics. DOI : 10.54052/jhds.v1n3.p309-316